In vitro and biomechanical screening of polyethylene glycol and poly(trimethylene carbonate) block copolymers for annulus fibrosus repair. (29th March 2017) - Long, Rose G.; Rotman, Stijn G.; Hom, Warren W.; Assael, Dylan J.; Illien‐Jünger, Svenja; Grijpma, Dirk W.; Iatridis, James C.
Abstract: Herniated intervertebral discs (IVDs) are a common cause of back and neck pain. There is an unmet clinical need to seal annulus fibrosus (AF) defects, as discectomy surgeries address acute pain but are complicated by reherniation and recurrent pain. Copolymers of polyethylene glycol with trimethylene carbonate (TMC) and hexamethylene diisocyanate (HDI) end‐groups were formulated as AF sealants as the HDI form covalent bonds with native AF tissue. TMC adhesives were evaluated and optimized using the design criteria: stable size, strong adherence to AF tissue, high cytocompatibility, restoration of IVD biomechanics to intact levels following in situ repair, and low extrusion risk. TMC adhesives had high adhesion strength as assessed with a pushout test (150 kPa), and low degradation rates over 3 weeks in vitro . Both TMC adhesives had shear moduli (220 and 490 kPa) similar to, but somewhat higher than, AF tissue. The adhesive with three TMC moieties per branch (TMC3) was selected for additional in situ testing because it best matched AF shear properties. TMC3 restored torsional stiffness, torsional hysteresis area and axial range of motion to intact states. However, in a failure test of compressive deformation under fixed 5 ° flexion, some herniation risk was observed with failure strength of 5.9 MPa compared with 13.5 MPa for intact samples; TMC3 herniated under cyclic organ culture testing. These TMC adhesives performed well during in vitro and in situ testing, but additional optimization to enhance failure strength is required to further this material to advanced screening tests, such as long‐term degradation. Copyright © 2016 John Wiley & Sons, Ltd.